Constraining beyond ΛCDM models with 21cm intensity mapping forecasted observations combined with latest CMB data. Issue 1 (11th January 2022) - Berti, M.; Spinelli, M.; Haridasu, B.S.; Viel, M.; Silvestri, A.
Abstract: We explore constraints on dark energy and modified gravity with forecasted 21cm intensity mapping measurements using the Effective Field Theory approach. We construct a realistic mock data set forecasting a low redshift 21cm signal power spectrum P 21 ( z, k ) measurement from the MeerKAT radio-telescope. We compute constraints on cosmological and model parameters through Monte-Carlo Markov-Chain techniques, testing both the constraining power of P 21 ( k ) alone and its effect when combined with the latest Planck 2018 CMB data. We complement our analysis by testing the effects of tomography from an ideal mock data set of observations in multiple redshift bins. We conduct our analysis numerically with the codes EFTCAMB /EFTCosmoMC, which we extend by implementing a likelihood module fully integrated with the original codes. We find that adding P 21 ( k ) to CMB data provides significantly tighter constraints on Ωc h 2 and H 0, with a reduction of the error with respect to Planck results at the level of more than 60%. For the parameters describing beyond ΛCDM theories, we observe a reduction in the error with respect to the Planck constraints at the level of ≲ 10%. The improvement increases up to ∼ 35% when we constrain the parameters using ideal, tomographic mock observations. We conclude that the power spectrum of the 21cm signal is sensitive to variations of the parameters describing the examined beyond ΛCDM models and, thus, P 21 ( k ) observations could help to constrain dark energy. The constraining power on such theories is improved significantly by tomography.